Multi-parameter MRI-based model for the prediction of early recurrence of hepatitis B-associated hepatocellular carcinoma after microwave ablation - Zhang, Ying; Yu, Jing-Jing; Chen, Wei; Liu, Bo; Wei, Xue-Fei; Wang, Zhao-Hui; Li, Xue; Gao, Shuai; Wang, Kai (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesTo establish and validate a multi-parameter model for the prediction of early recurrence in patients with hepatitis B-associated hepatocellular carcinoma (HBV-HCC) after microwave ablation.MethodsThis study retrospectively reviewed the clinical features and preoperative magnetic resonance imaging (MRI) scans of 166 patients with HBV-HCC who underwent microwave ablation at two hospitals. The training cohort comprised 116 patients from the first hospital (n = 116; mean age, 56 years; 84 male patients), while 50 patients from the second hospital constituted the external validation cohort (n = 50; mean age, 60 years; 38 male patients). A transformer-based deep learning network was used to fuse images from multi-sequence MRI and predict recurrence within 1 year after microwave ablation. Additionally, a nomogram based on deep learning radiomics and clinical features was developed and externally validated in a validation group from a second hospital.ResultsThe combined model was better than the clinical model and MRI model in predicting early recurrence of hepatitis B-associated hepatocellular carcinoma within 1 year after microwave ablation. Nomograms based on joint models include aspartate aminotransferase, portal hypertension, and deep learning-based radiomics scores. The areas under curves of the models in the training group and the validation group were 0.868 (95% CI: 0.793–0.924) and 0.842 (95% CI: 0.711–0.930), respectively, indicating high prediction ability. The results of decision curve analysis showed that the combined model had good clinical application value and correction effect.ConclusionsOur nomogram combined with clinical features and preoperative magnetic resonance imaging features effectively predicted early recurrence of hepatitis B-associated hepatocellular carcinoma within 1 year after microwave ablation.